Attitude in Korean Entertainment Industry News Texts on SBS News: An Appraisal Study - Uswatun Hasanah; Velayeti Nurfitriana Ansas; Arif Husein Lubis (Universitas Nusantara PGRI Kediri, 2026)
This study examines attitude in ten SBS News articles on issues in the Korean entertainment industry using Martin and White’s Appraisal framework. The analysis focuses on the attitude subsystem realized explicitly (inscribed) through evaluative lexis, while engagement and graduation are treated as supporting resources to explain the source of evaluative voices and the intensification or softening of meaning when relevant. The data are analyzed qualitatively through sentence-level coding, complemented by mapping the frequency and distribution of categories across texts to capture broader tendencies. The findings show that evaluation is most strongly realized through judgement, followed by appreciation and affect. In terms of polarity, the attitudes expressed are predominantly negative, particularly within judgement that centres on the propriety of actors’ actions and behaviour. In addition, evaluation is frequently conveyed through quotations or attribution, allowing evaluative meanings to remain salient while being framed as others’ voices and maintaining an appearance of journalistic caution. Overall, the findings indicate that SBS News coverage of issues in the Korean entertainment industry tends to construct evaluation primarily through social assessment of actors and their actions.